Hard carbon-graphite composite negative electrode material for sodium-ion battery and preparation method of hard carbon-graphite composite negative electrode material
The hard carbon-graphite composite anode material designed with a core-shell structure and a gradient buffer layer solves the problems of low electronic conductivity, difficulty in sodium ion insertion, and high volume expansion rate in sodium-ion batteries, achieving high cycle stability and high energy density, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202511710810.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-20
- Publication Date
- 2026-02-06
AI Technical Summary
Existing hard carbon and graphite composite anode materials have problems such as low electronic conductivity, difficulty in sodium ion intercalation, high volume expansion rate, and weak interfacial bonding in sodium-ion batteries, resulting in poor cycle stability. Moreover, the preparation process is complex and costly, making it difficult to industrialize.
A core-shell structured hard carbon-graphite composite anode material is used, with a graphite core as the inner core and a hard carbon shell as the outer shell. A nano-silicate modifier forms a gradient buffer layer at the interface. Combined with ball milling, dispersion and low-temperature heat treatment processes, a composite material with good conductivity, high sodium storage capacity and resistance to volume expansion is formed.
It achieves a synergy between high conductivity and high sodium storage capacity, reduces the volume expansion rate to below 5%, maintains a high capacity retention rate after 2000 cycles, improves the material's energy density, and has a simple and low-cost preparation process, making it suitable for continuous production.
Smart Images

Figure CN121484027A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and in particular to a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method. Background Technology
[0002] Sodium-ion batteries, due to the abundance, wide distribution, and low cost of sodium resources, have shown significant advantages in large-scale energy storage and low-speed electric vehicles, becoming an important supplementary direction for lithium-ion batteries. As the core component of sodium-ion batteries, the anode material's sodium storage performance, conductivity, and structural stability directly determine the battery's energy density, cycle life, and rate performance. Currently, hard carbon materials, with their abundant nanopores and defect structures, can provide sufficient sodium-ion insertion / extraction active sites, achieving a sodium storage capacity of 300-400 mAh / g, making them one of the mainstream candidate materials for sodium-ion battery anodes. However, hard carbon has a much lower electronic conductivity than graphite, and its volume expansion rate during sodium-ion insertion / extraction is as high as 15%-25%, easily leading to electrode cracking, active material shedding, and poor cycle stability.
[0003] Graphite materials possess excellent electronic conductivity and a layered crystal structure, with a compaction density reaching [missing value]. While graphite interlayer spacing is only 0.335 nm and sodium ion radius is approximately 0.102 nm, sodium ions are difficult to effectively embed between graphite layers due to steric hindrance, resulting in sodium storage capacity typically below 100 mAh / g, which cannot meet high-capacity requirements. Existing hard carbon-graphite composite solutions mostly employ physical mixing, leading to weak interfacial bonding and easy interface separation during cycling, resulting in broken electron conduction pathways. Some studies introduce modifiers, but uneven dispersion prevents the formation of a continuous buffer structure, limiting the volume expansion suppression effect. Furthermore, existing preparation processes often rely on specialized equipment such as high-energy ball milling (speed > 800 rpm) and plasma coating, or require multiple chemical modifications, making operation complex and costly, hindering large-scale continuous production and restricting the industrialization of composite anode materials. Therefore, this invention proposes a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method to address the problems existing in the prior art. Summary of the Invention
[0004] To address the aforementioned issues, this invention proposes a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method. Employing a core-shell structure, the high conductivity of the graphite core and the high sodium storage capacity of the hard carbon shell are fully synergistic, overcoming the shortcomings of single-material construction. The nano-silicate gradient buffer layer reduces the volume expansion rate to below 5%, resulting in a higher capacity retention rate after 2000 cycles compared to unmodified composite materials. Simultaneously, the graphite core enhances the material's compaction density and energy density.
[0005] To achieve the objective of this invention, the invention is implemented through the following technical solution: a hard carbon graphite composite negative electrode material for sodium-ion batteries, comprising the following mass ratio components: 50-80 parts graphite core, 15-45 parts hard carbon shell, 1-5 parts nano-silicate modifier, and 1-3 parts binder.
[0006] The composite anode material has a core-shell composite structure, with a graphite core as the core and a hard carbon shell covering the surface of the graphite core. A nano-silicate modifier forms a gradient buffer layer at the hard carbon-graphite interface. The graphite core provides a high electronic conductivity pathway and structural support, the hard carbon shell provides active sites for sodium ion insertion / extraction, and the nano-silicate modifier suppresses volume expansion during sodium ion insertion / extraction.
[0007] A further improvement is made in that the particle size of the graphite core is... The particle size of the hard carbon shell is .
[0008] A further improvement is that the nano-silicate modifier is one or both of nano-kaolin and nano-montmorillonite, and the particle size of the nano-silicate modifier is 50-200nm.
[0009] A further improvement is that the adhesive is one or both of polyvinyl alcohol and sodium carboxymethyl cellulose.
[0010] A method for preparing a hard carbon-graphite composite anode material for sodium-ion batteries includes the following steps:
[0011] S1: Pretreatment, the graphite raw material, hard carbon raw material and nano silicate modifier are dried separately to remove moisture and impurities;
[0012] S2: Ball milling activation, which involves mixing and ball milling the pretreated raw materials to increase the specific surface area and improve interfacial bonding;
[0013] S3: Mix and disperse, add binder and dispersion medium, and stir to form a uniform slurry;
[0014] S4: Heat treatment. After the slurry is dried, it is heat treated under a protective atmosphere to form a core-shell structure and a gradient buffer layer. After cooling, a composite anode material is obtained.
[0015] A further improvement is that, in S2, the ball milling speed is 200-500 rpm and the ball milling time is 1-4 hours.
[0016] A further improvement is made in S2, where, during the ball milling activation process, the activation effect of the raw materials is ensured by controlling the ball milling energy density, which is calculated using the following formula:
[0017] ,
[0018] Where: E is the ball milling energy density, in kJ / g, representing the mechanical energy gained per unit mass of material during ball milling, with a value range of 0.8-2.5 kJ / g; n is the ball mill rotation speed, in r / s, calculated from the set rotation speed of the ball mill, with the conversion formula n = set rotation speed ÷ 60; m is the mass of a single grinding ball, in g, with the grinding ball material being agate or zirconium oxide, and the mass range of a single ball being 0.5-5g; r is the radius of the grinding ball, in cm, with the grinding ball diameter ranging from 5-15mm, so the radius corresponds to 0.25-0.75cm; t is the ball milling time, in s, calculated from the ball milling time set in S2, with the conversion formula t = set time × 3600; M is the total mass of the material ball-milled in S2, in g, which is the sum of the masses of the pretreated graphite raw material, hard carbon raw material, and nano-silicate modifier.
[0019] A further improvement is that, in step S3, the dispersion medium is one or both of deionized water and ethanol, and the mass ratio of the dispersion medium to the mixed raw materials is 2-5:1.
[0020] A further improvement is that, in step S4, the protective atmosphere is one or both of nitrogen and argon, the heat treatment temperature is 500-800℃, and the holding time is 2-6h.
[0021] A further improvement is that, in step S4, the cooling rate after heat treatment is 5-10℃ / min, and the composite anode material is obtained after cooling to room temperature.
[0022] The beneficial effects of this invention are as follows:
[0023] 1. This invention adopts a core-shell structure, which fully synergizes the high conductivity of the graphite core with the high sodium storage capacity of the hard carbon shell, solving the defects of single materials. The nano-silicate gradient buffer layer can reduce the volume expansion rate to below 5%. Compared with the unmodified composite material, the capacity retention rate is higher after 2000 cycles. At the same time, the graphite core improves the compaction density and energy density of the material.
[0024] 2. This invention adopts a four-step process of pretreatment, ball milling, dispersion and heat treatment, which does not require special equipment. The parameters such as ball milling speed and heat treatment temperature have a wide range and are easy to control. The protective atmosphere avoids the oxidation of raw materials and ensures purity. The dispersion medium uses deionized water or ethanol, which is low in cost and environmentally friendly. It is suitable for continuous production line layout and improves production efficiency.
[0025] 3. This invention adopts an interface gradient buffer layer design, which breaks through the technical limitations of existing simple mixing or single-layer coating, and realizes the three-in-one function of conductivity, sodium storage and anti-expansion. The preparation process combines ball milling activation and low temperature heat treatment, which ensures the interface bonding strength while avoiding the destruction of hard carbon structure. Compared with high temperature sintering process, it reduces energy consumption, and the material's coulombic efficiency is improved to more than 85% for the first time, which is significantly better than existing composite anode materials. Attached Figure Description
[0026] Figure 1 This is a flowchart of the present invention. Detailed Implementation
[0027] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0028] Example 1
[0029] according to Figure 1 As shown, this embodiment proposes a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method:
[0030] Material composition:
[0031] 60 parts of graphite cores (particle size) ), 35 parts of hard carbon shell (particle size) ), 3 parts nano-kaolin (particle size 100nm), 2 parts polyvinyl alcohol (PVA).
[0032] Preparation steps:
[0033] S1. Pretreatment: Graphite, hard carbon, and nano-kaolin were dried in an 80℃ forced-air drying oven for 4 hours;
[0034] S2. Ball milling activation: Add the mixed raw materials to the ball mill, and mill at 300 rpm for 2 hours;
[0035] S3. Mixing and dispersing: Add PVA and deionized water (mass ratio 3:1), stir at 500 rpm for 1 hour;
[0036] S4. Heat treatment: Dry at 60℃ for 12 hours, then purge with argon gas in a tube furnace and hold at 600℃ for 4 hours. Cool to room temperature.
[0037] Performance testing:
[0038] Assembled button-type sodium-ion batteries, 1C rate test: initial discharge capacity 380mAh / g, capacity retention rate 92% after 2000 cycles, compaction density 1.6g / cm³.
[0039] Example 2
[0040] according to Figure 1 As shown, this embodiment proposes a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method:
[0041] Material composition:
[0042] 70 parts of graphite cores (particle size) ), 25 parts of hard carbon shell (particle size) ), 2 parts of nano-montmorillonite (particle size 150nm), and 1.5 parts of sodium carboxymethyl cellulose (CMC).
[0043] Preparation steps:
[0044] S1. Pretreatment: Dry at 100℃ for 3 hours;
[0045] S2. Ball milling activation: 400 rpm, ball milling for 3 hours;
[0046] S3. Mixing and dispersing: Add CMC and ethanol (mass ratio 4:1), stir at 600 rpm for 1.5 h;
[0047] S4. Heat treatment: Dry at 70℃ for 10 hours, under nitrogen protection, and hold at 700℃ for 3 hours. cool down.
[0048] Performance testing:
[0049] 1C rate: initial discharge capacity 370mAh / g, capacity retention rate 90% after 2000 cycles, compaction density 1.7g / cm³.
[0050] Example 3
[0051] according to Figure 1 As shown, this embodiment proposes a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method:
[0052] Material composition:
[0053] 50 portions of graphite cores (particle size) ), 45 parts of hard carbon shell (particle size) ), 4 parts of nano-kaolin-montmorillonite mixed modifier (1:1, particle size 80nm), and 3 parts of PVA.
[0054] Preparation steps:
[0055] S1. Pretreatment: Dry at 90℃ for 5 hours;
[0056] S2. Ball milling activation: 250 rpm, ball milling for 4 hours;
[0057] S3. Mixing and dispersing: Add PVA and deionized water-ethanol (1:1, mass ratio 2:1), stir at 400 rpm for 2 hours;
[0058] S4. Heat treatment: Dry at 65℃ for 11 hours, under argon protection, hold at 550℃ for 5 hours, and cool at 6℃ / min.
[0059] Performance testing:
[0060] 1C rate: initial discharge capacity 390mAh / g, capacity retention rate 93% after 2000 cycles, compaction density 1.5g / cm³.
[0061] Example 4
[0062] according to Figure 1 As shown, this embodiment proposes a hard carbon-graphite composite anode material for sodium-ion batteries and its preparation method:
[0063] Material composition:
[0064] 75 parts of graphite cores (particle size) ), 18 parts of hard carbon shell (particle size) ), 3 parts nano illite (particle size 120nm), 2 parts sodium carboxymethyl cellulose (CMC)-polyvinyl alcohol (PVA) mixed binder (mass ratio 1:1).
[0065] Preparation steps:
[0066] S1. Pretreatment: The graphite raw material, hard carbon raw material, and nano illite were placed in a 95℃ vacuum drying oven and dried for 4.5 hours to further reduce residual moisture (the vacuum environment can reduce the water adsorbed on the surface of the raw materials, which is more conducive to subsequent interface bonding than air drying).
[0067] S2. Ball milling activation: Mix the pretreated raw materials according to the weight proportions, add them to the ball mill (the grinding balls are made of zirconia material and have a diameter of 10mm), set the ball milling speed to 450rpm, and the ball milling time to 2.5h to balance material refinement and energy consumption;
[0068] S3. Mixing and Dispersion: Add the mixed binder and dispersion medium (deionized water-ethanol, mass ratio 2:1) to the ball-milled mixed raw materials. The mass ratio of dispersion medium to mixed raw materials is 3.5:1. Stir at a stirring speed of 550 rpm for 1.2 h to form a uniform and stable slurry (avoid stirring too fast to prevent binder agglomeration).
[0069] S4. Heat treatment: The slurry was dried in a 75℃ forced-air drying oven for 11.5h, then placed in a tube furnace and a nitrogen-argon mixed protective atmosphere (volume ratio 1:1, taking into account both cost and anti-oxidation effect) was introduced. The temperature was raised to 650℃ and held for 3.5h, and then cooled to room temperature at a cooling rate of 9℃ / min to obtain hard carbon / graphite composite anode material.
[0070] Performance testing
[0071] Assembled coin cell sodium-ion batteries (electrolyte is 1 mol / L NaClO4-propylene carbonate / dimethyl carbonate, volume ratio 1:1), 1C rate test: initial discharge capacity 365 mAh / g, capacity retention rate 89% after 2000 cycles, compaction density 1.65 g / cm³ (high proportion of graphite cores and moderate particle size, compaction density between Example 2 and Example 1, which is consistent with the component design logic).
[0072] This invention employs a core-shell structure, fully synergistically combining the high conductivity of the graphite core with the high sodium storage capacity of the hard carbon shell, overcoming the shortcomings of single-material formulations. The nano-silicate gradient buffer layer reduces the volume expansion rate to below 5%, resulting in a higher capacity retention rate after 2000 cycles compared to unmodified composite materials. Simultaneously, the graphite core enhances the material's compaction density and energy density. Furthermore, this invention utilizes a four-step process—pretreatment, ball milling, dispersion, and heat treatment—requiring no special equipment. The ball milling speed and heat treatment temperature parameters have a wide range, making operation easy to control. A protective atmosphere prevents raw material oxidation, ensuring purity. The dispersion medium uses deionized water or ethanol, which is low-cost and environmentally friendly, suitable for continuous production line layouts, and improves production efficiency. Moreover, this invention employs an interface gradient buffer layer design, overcoming the limitations of existing simple mixing or single-layer coating technologies. It achieves integrated functionality of conductivity, sodium storage, and anti-expansion. The combination of ball milling activation and low-temperature heat treatment in the preparation process ensures interfacial bonding strength while avoiding damage to the hard carbon structure. Compared to high-temperature sintering processes, it reduces energy consumption, and the material's initial coulombic efficiency is increased to over 85%, significantly superior to existing composite anode materials.
[0073] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A hard carbon-graphite composite anode material for sodium-ion batteries, characterized in that: It includes the following components in the following mass ratio: 50-80 parts graphite core, 15-45 parts hard carbon shell, 1-5 parts nano-silicate modifier, and 1-3 parts binder; The composite anode material has a core-shell composite structure, with a graphite core as the core and a hard carbon shell covering the surface of the graphite core. A nano-silicate modifier forms a gradient buffer layer at the hard carbon-graphite interface. The graphite core provides a high electronic conductivity pathway and structural support, the hard carbon shell provides active sites for sodium ion insertion / extraction, and the nano-silicate modifier suppresses volume expansion during sodium ion insertion / extraction.
2. The hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 1, characterized in that: The particle size of the graphite core is The particle size of the hard carbon shell is .
3. The hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 1, characterized in that: The nano-silicate modifier is one or both of nano-kaolin and nano-montmorillonite, and the particle size of the nano-silicate modifier is 50-200nm.
4. The hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 1, characterized in that: The adhesive is one or both of polyvinyl alcohol and sodium carboxymethyl cellulose.
5. A method for preparing a hard carbon-graphite composite anode material for sodium-ion batteries, applied to the hard carbon-graphite composite anode material for sodium-ion batteries described in any one of claims 1-4, characterized in that, Includes the following steps: S1: Pretreatment, the graphite raw material, hard carbon raw material and nano silicate modifier are dried separately to remove moisture and impurities; S2: Ball milling activation, which involves mixing and ball milling the pretreated raw materials to increase the specific surface area and improve interfacial bonding; S3: Mix and disperse, add binder and dispersion medium, and stir to form a uniform slurry; S4: Heat treatment. After the slurry is dried, it is heat treated under a protective atmosphere to form a core-shell structure and a gradient buffer layer. After cooling, a composite anode material is obtained.
6. The method for preparing a hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 5, characterized in that: In step S2, the ball milling speed is 200-500 rpm, and the ball milling time is 1-4 hours.
7. The method for preparing a hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 5, characterized in that: In step S2, during the ball milling activation process, the activation effect of the raw materials is ensured by controlling the ball milling energy density, which is calculated according to the following formula: , Where: E is the ball milling energy density, in units of... This characterizes the mechanical energy gained per unit mass of material during ball milling, and its value ranges from [value range missing]. n is the rotational speed of the ball mill, in r / s, which is calculated from the set rotational speed of the ball mill using the formula n = set rotational speed ÷ 60; m is the mass of a single grinding ball, in g, with the grinding ball material being agate or zirconium oxide, and the mass range of a single ball being 0.5-5g; r is the radius of the grinding ball, in cm, with the grinding ball diameter ranging from 5-15mm, so the radius corresponds to 0.25-0.75cm; t is the ball milling time, in s, which is calculated from the ball milling time set in S2 using the formula t = set time × 3600; M is the total mass of the material being ball-milled in S2, in g, which is the sum of the masses of the pretreated graphite raw material, hard carbon raw material, and nano-silicate modifier.
8. The method for preparing a hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 5, characterized in that: In step S3, the dispersion medium is one or both of deionized water and ethanol, and the mass ratio of the dispersion medium to the mixed raw materials is 2-5:
1.
9. A method for preparing a hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 5, characterized in that: In step S4, the protective atmosphere is one or both of nitrogen and argon, the heat treatment temperature is 500-800℃, and the holding time is 2-6h.
10. A method for preparing a hard carbon-graphite composite negative electrode material for sodium-ion batteries according to claim 5, characterized in that: In step S4, the cooling rate after heat treatment is: After cooling to room temperature, a composite anode material is obtained.